Bilateral Mastoiditis Complicated by Unilateral Zygomaticitis – Rare form, Challenging Diagnosis (London Journal of Medical and Health Research, 2026)
Introduction: Bilateral mastoiditis complicated by unilateral zygomaticitis is an exceptional clinical entity, rarely described in the literature. Although the incidence of complications of acute otitis media has decreased significantly with the introduction of modern antibiotic therapy, atypical forms of bone extension remain a diagnostic challenge. The association of bilateral mastoid involvement with zygomatic bone involvement can cause a non-specific clinical picture, delaying diagnosis and the establishment of appropriate treatment.Materials and Methods: In this case study we present a 41-year-old male patient who suffered bilateral mastoiditis complicated by unilateral zygomaticitis following a chronic rhinosinusal pathology in exacerbation. He presented with accusations of: pronounced headache, bilateral otodynia, suppurative otorhea, swelling in the projection of the zygomatic bone on the left, bilateral hearing loss. The patient underwent bilateral petromastoid clearance surgery with incision and drainage of the zygomatic collection on the left.Results: Epidemiological data from the literature indicate that acute mastoiditis in adults accounts for approximately 10–15% of all mastoiditis cases. The overall incidence is estimated at less than 0.5 cases per 100,000 adults annually in countries with access to modern health services. Although antibiotic therapy has dramatically reduced mortality associated with mastoiditis (from 20–30% in the pre-antibiotic era to less than 1% today), it remains a pathology with a significant risk of extracranial complications (subperiosteal abscess, apical-cervical mastoiditis, petrositis) and endocranial complications (meningitis, lateral sinus thrombosis, brain abscess). Although less common, acute mastoiditis remains a pathology of current interest, with a significant impact on public health, requiring a multidisciplinary and updated approach to the new infectious challenges. We present a rare case of such an otic pathology in a 41-year-old male patient who suffered bilateral mastoiditis complicated by unilateral zygomaticitis as a result of enduring a chronic acute rhinosinusal pathology.Conclusions: Acute mastoiditis, although rare in the age of antibiotics, continues to be an otological emergency, with significant potential for endocranial and extracranial complications, especially in cases not properly treated.
Keywords: Hearing loss.; mastoiditis; otorhea; zygomaticitis